Electroactive materials for organic electronics: preparation strategies, structural aspects and characterization techniques - Pron, Adam; Gawrys, Pawel; Zagorska, Malgorzata; Djurado, David; Demadrille, Renaud (Chemical Society reviews, 2010)
This critical review discusses specific chemical and physicochemical requirements which must be met for organic compounds to be considered as promising materials for applications in organic electronics. Although emphasis is put on molecules and macromolecules suitable for fabrication of field effect transistors (FETs), a large fraction of the discussed compounds can also be applied in other organic or hybrid (organic-inorganic) electronic devices such as photodiodes, light emitting diodes, photovoltaic cells, etc. It should be of interest to chemists, physicists, material scientists and electrical engineers working in the domain of organic electronics (423 references).